The population of high-mass X-ray binaries in the LMC detected during the first eROSITA all-sky survey - Kaltenbrunner, David; Maitra, Chandreyee; Haberl, Frank; Vasilopoulos, Georgios (2024)
The Magellanic Clouds are our closest star-forming galaxies with low Galactic foreground absorption. This makes them a unique laboratory to study the population of high-energy sources. The SMC hosts a large population of Be/X-ray binaries associated with high star formation activity 25-40 Myr ago. It has been proposed that the HMXB population in the LMC is associated with more recent star formation. However, due to the large angular extent and resulting insufficient coverage of the LMC, this association with SFR is not well established yet. An essential asset for studying the HMXB population in the entire LMC was the launch of eROSITA. eROSITA scans the sky in great circles crossing at the ecliptic poles. Due to the vicinity of the south-ecliptic pole, sources in the LMC are monitored for up to several weeks during each all-sky survey, leading to a deep total exposure and the possibility of studying long-term temporal behaviour. This allowed us to discover several new HMXBs, verify candidate HMXBs and construct a complete, flux-limited catalogue. During my presentation, I will first focus on HMXB population properties in the LMC. Then I will discuss individual systems we discovered with eROSITA, such as a Be-WD and an SFXT candidate.